Preparation, characterization and cytotoxic evaluation of bovine serum albumin nanoparticles encapsulating 5-methylmellein: A secondary metabolite isolated from Xylaria psidii. Issue 23 (1st December 2017) - Arora, Divya; Kumar, Amit; Gupta, Prasoon; Chashoo, Gousia; Jaglan, Sundeep
Graphical abstract: Abstract: In this study, 5-methylmellein (5-MM) loaded bovine serum albumin nanoparticles (BSA NPs) were developed using desolvation technique. The developed nanoparticles were characterized for their mean particle size, polydispersity, zeta potential, loading efficiency, X-ray diffractometry (XRD), differential scanning calorimetry (DSC) and release profile. The developed nanoparticles were spherical in shape under transmission electron microscopy (TEM) and atomic force microscopy (AFM). The developed 5-MM loaded BSA NPs demonstrated a mean particle size with a diameter of 154.95 ± 4.44 nm. The results from XRD and DSC studies demonstrated that the crystal state of the 5-MM was converted to an amorphous state in polymeric matrix. The encapsulation and loading efficiency was found to be 73.26 ± 4.48% and 7.09 ± 0.43%. The in vitro cytotoxicity in human prostate cancer cell line( PC-3), human colon cancer cells (HCT-116) and human breast adenocarcinoma cell line (MCF-7) cells demonstrated enhanced cytotoxicity of 5-MM BSA NPs as compared to native 5-MM after 72-h treatment. The enhancement in cytotoxicity of 5-MM BSA NPs was also supported by increase in cellular apoptosis, mitochondrial membrane potential loss and generation of high reactive oxygen species (ROS). In conclusion, these findings collectively indicated that BSA nanoparticles may serve as promising drug delivery system for improving the efficacy of 5-methylmellein.